Images of person in an Amerindian society. An ethnographic account of Kuna woodcarving - Paolo Fortis (Journal de la Société des Américanistes)
Images of person in an Amerindian society. An ethnographic account of Kuna woodcarving. The long debated problem of representation in Amerindian art discussed by Boas, Kroeber and Lévi-Strauss is reconsidered in this article through an ethnographic account of Kuna woodcarving. By analysing the making of wooden anthropomorphic figures and the Kuna exegesis of it, along with some comparative examples from other Amerindian societies, this article argues for an understanding of the sculptural representation of the human figure as an instantiation of alterity. Kuna wooden figures, it is argued, are metonymically related to soul images and instantiate the more general Amerindian principle of a continuity of souls behind a discontinuity of bodies. Explored through art the theme of alterity, both at the level of the person and the cosmological world, provides a framework to look at ideas of birth and death, and the centrality of kinship in the creation of human bodies.